Пламя и цветок: роман / К. Вудивисс ; пер. с англ. У. В. Сапциной - Вудивисс Кэтлин (АСТ, 2004)
Экземпляры: Ф-18 (20190830☮) / Инвентарный номер: 94440 / Цена: / Сис.шифр: 84(7=432.1)-44 / Авт.знак: В 88 / ББК: 84(7=432.1)-44